Quality-improvement project to reduce actual fasting times for fluids and solids before induction of anaesthesia. - Witt, Lars; Lehmann, Barbara; Sümpelmann, Robert; Dennhardt, Nils; Beck, Christiane E. (BMC Anesthesiology, 2021)
Background: Despite well-defined recommendations, prolonged fasting times for clear fluids and solids are still common before elective surgery in adults. Extended fasting times may lead to discomfort, thirst, hunger and physiological dysfunctions. Previous studies have shown that prolonged fasting times are frequently caused by patients being misinformed as well as inadequate implementation of the current guidelines by medical staff. This study aimed to explore how long elective surgery patients fast in a German secondary care hospital before and after the introduction of an educational note for patients and re-training for the medical staff. Methods: A total of 1002 patients were enrolled in this prospective, non-randomised interventional study. According to the power calculation, in the first part of the study actual fasting times for clear fluids and solids were documented in 502 consecutive patients, verbally instructed as usual regarding the recommended fasting times for clear fluids (2 h) and solids (6 h). Subsequently, we implemented additionally to the verbal instruction a written educational note for the patients, including the recommended fasting times. Furthermore, the medical staff was re-trained regarding the fasting times using emails, newsletters and employee meetings. Thereafter, another 500 patients were included in the study. We hypothesised, that after these quality improvement procedures, actual fasting times for clear fluids and solids would be more accurate on time. Results: Actual fasting times for clear fluids were in the median 11.3 (interquartile range 6.8–14.3; range 1.5–25.5) h pre-intervention, and were significantly reduced to 5.0 (3.0–7.2; 1.5–19.8) h after the intervention (median difference (95%CI) − 5.5 (− 6.0 to − 5.0) h). The actual fasting times for solids also decreased significantly, but only from 14.5 (12.1–17.2; 5.4–48.0) h to 14.0 (12.0–16.3; 5.4–32.0) h after the interventions (median difference (95%CI) − 0.52 (− 1.0 to − 0.07) h). Conclusions: The study showed considerably extended actual fasting times in elective adult surgical patients, which were significantly reduced by simple educational/training interventions. However, the actual fasting times still remained considerably longer than defined in recommended guidelines, meaning further process optimisations like obligatory fluid intake in the early morning are necessary to improve patient comfort and safety in future. Trial registration: German registry of clinical studies (DRKS-ID: DRKS 00020530, retrospectively registered).